SOCIALIZATION OF IMPLEMENTATION OF ATHEISM-BASED CIRCUIT LEARNING MODEL IN ELEMENTARY SCHOOLS: SOSIALISASI IMPLEMENTASI MODEL PEMBELAJARAN SIRKUIT BERBASIS AKIDAH DI SEKOLAH DASAR - Pungki Indarto; Gatot Jariono; Muhammad Faiz; Rafli Muhammad; Dwi Endri Mei Minawati (Yayasan Education and Social Center, 2021)
The problem of interest and inculcating attitudes in learning during the new habituation period from online to offline requires a suitable approach method according to the characteristics of the growth and development of students at the elementary school level. This service aims to provide the application of science resulting from the development of faith-based circuit learning models in physical education, sports, and health. The method used is to provide socialization and implementation to the Muhammadiyah Elementary School teachers for the Baturan Special Program. This dedication resulted in applying the circuit learning method based on the creed of mini volleyball in grade 4 elementary school. Circuit learning consists of 3 posts, and each post consists of 3 learning approaches by playing. Each game has AKIDAH values (Analytical, Creative, Innovative, Demonstrative, Active, and Humanist). Implementations in circuit-based learning include 1) games without tools (black-green, cu, fishnets); 2) games with tools (shoot deer, bowling bottles, grab me); 3) mini-volleyball approach games (upper pass, underpass, underserve). The faith-based circuit learning model increases participation, interest, and motivation in participating in learning in elementary schools